Circular economy for “blue skies” in building resilient cities—towards the UN 2030 Agenda for Sustainable Development Goals - Khajuria, Anupam; Verma, Prabhat (Frontiers in Sustainability, 2025)
Cities facing direct risks and vulnerabilities to get damaged and harmed due to natural disasters are increasingly expected to implement a distinctive and positive role in promoting resilience. Among many other factors, a key component in sustaining urban resilience is the cleanliness of the air, which contributes to achieving a blue sky. In this context, this Article aims to discuss the strategies grounded on the circular economy approach, which are influential in addressing various forms of air pollution. In our approach, we consider the manifold origins of air pollution, including factors such as rapid urbanization, waste generation, industrial and wastewater pollutants, vehicular emissions, and wildfires that pose a complex challenge. Our recommendations to deal with these challenges revolve around addressing them by embracing circular economy strategies, which is crucial for achieving clean air in urban areas. We discuss the importance of clean air for resilient cities and outline critical strategies for building resilience through circular economy practices. Aligning with the United Nations Sustainable Development Goals, this article sheds light on the vital role of the circular economy in realizing blue skies for resilient cities.